Muatan Lokal dalam Pembelajaran di Sekolah Dasar - Juhadi Juhadi; Laelia Nurpratiwiningsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
Education and life are the relationship between process and content, as well as the process of adopting culture in the sense of human civilization. With this, there is a need for understanding and preservation that needs to be instilled in children in learning at school. The method used is a qualitative method in the form of description. Data collection using interviews, observations and documentation, through the silencing of techniques and data analysis starts from data collection, data reduction, data presentation and conclusions. This research was conducted at SD Negeri Cigadung 03, with informants of teachers and students. The results of the discussion showed that the social studies teaching material for grade IV elementary school was related to stories about my area, my Indonesia is rich in culture, me and my needs, and building a civilized society. In this regard, there needs to be implications that can be applied in learning about local content in Brebes district. This is done with the intention of being the direction of the child's consciousness related to learning that corresponds to real life. Students can learn about salted egg, Sundanese language, Javanese, khaul, kerigan, sintren, calung, burok art, kuntulan, brebes mask dance, and pandansari mongrove forest